“The Plague Shall Be Lifted": Representations of East and West in NOSFERATU (2024) - Monika Leferman (Linguaculture)
Robert Eggers' critically acclaimed Nosferatu (2024) revisits the myth of the vampire in a visually stunning masterpiece that revitalizes one of the most iconic myths of modern times. Rooted in Eastern European folklore and the literary imagination of centuries past, the vampire fascinates and inspires artists today. Bram Stoker's Dracula (1897) popularised the vampire in the Western imagination in a novel in which East and West are presented as spatial embodiments of the dichotomy between civilised and savage. This paper aims to analyse the depiction of East and West in Nosferatu (2024), arguing that while such a political representation is not Eggers' primary aim, the film successfully inverts the narrative according to which the East is savage while the West is the civilised counterpart while also integrating forms of othering, namely spatial, cultural, and corporeal. This study also aims to highlight the implications of the film in terms of its representation of East and West while providing a deeper understanding of the development of the vampire myth in cinema.